2005
DOI: 10.1177/0093854805278414
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Factor Models on the PCL-R With Mentally Disordered Offenders

Abstract: For more than a decade, researchers and practitioners have generally accepted a two-factor model for the Psychopathy Checklist-Revised (PCL-R) composed of core personality features and an antisocial lifestyle. Very recently, Cooke and Michie (2001) proposed a three-factor solution that divided the core personality features into two dimensions while eliminating antisocial behavior. This study of male, mentally disordered offenders ( N = 96) directly compared factor models via confirmatory factor analysis (CFA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 42 publications
5
57
1
1
Order By: Relevance
“…Consistent with recent research on the underpinnings of psychopathy, in this study, we demonstrated that psychopathy can be represented in terms of interpersonal, affective, lifestyle, and antisocial dimensions (Hare & Neumann, in press;Hill et al, 2004;Neumann et al, 2005;Vitacco, Rogers, Neumann, Harrison, & Vincent, 2005). Of note, the poor results for the two-factor model are consistent with previous findings (Cooke & 80 VITACCO, NEUMANN, CALDWELL, LEISTICO, VAN RYBROEK Michie, 2001; Darke, Kaye, Finlay-Jones, & Hall, 1998;Kosson et al, 2002;McDermott et al, 2000) that have questioned the viability of the two-factor model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with recent research on the underpinnings of psychopathy, in this study, we demonstrated that psychopathy can be represented in terms of interpersonal, affective, lifestyle, and antisocial dimensions (Hare & Neumann, in press;Hill et al, 2004;Neumann et al, 2005;Vitacco, Rogers, Neumann, Harrison, & Vincent, 2005). Of note, the poor results for the two-factor model are consistent with previous findings (Cooke & 80 VITACCO, NEUMANN, CALDWELL, LEISTICO, VAN RYBROEK Michie, 2001; Darke, Kaye, Finlay-Jones, & Hall, 1998;Kosson et al, 2002;McDermott et al, 2000) that have questioned the viability of the two-factor model.…”
Section: Discussionsupporting
confidence: 91%
“…The different pattern of results between the three-and four-factor model SEMs are similar to the findings of , whereby the parameters for the other psychopathy factors take on greater strength when the Antisocial Psychopathy factor is included in the model. We interpret this finding to indicate that the antisocial facet plays a central role in the underlying factor structure of psychopathy (see Hare, 2003;Neumann et al, 2005;Vitacco, Rogers, et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Hence, most importantly, the PPI-R needs factor structure improvement which should be started at item level. (Vitacco, Rogers, Neumann, Harrison, & Vincent, 2005).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…U četverofaktor-skoj strukturi SRP-a III tri faktora odgovaraju Cookeovoj i Michievoj trofaktorskoj strukturi, a četvrti faktor predstavlja antisocijalni faktor. Niz kasnijih istraživanja potvrdio je če-tverofaktorsku strukturu (Hill, Neumann i Rogers, 2004;Neumann i sur., 2005;Vitacco, Rogers, Neumann, Harrison i Vincent, 2005). Neka su istraživanja, koristeći se multiplom regresijom, pokazala da četverofaktorska struktura ima bolju prediktivnu valjanost, npr.…”
Section: Mjerenje Psihopatskoga Poremećaja Ličnostiunclassified